Analisis Faktor Penentu Kinerja Atlet Voli Pantai: Sebuah Kajian Literatur - Murtadho, Muhammad Muchid; Subagio , Irmantara; Widodo, Achmad; Muhammad, Muhammad; Sulistyarto, Soni (Jurnal Porkes, 2025)
This study aims to analyze the determinants of beach volleyball athletes' performance through a literature review. This study identified various aspects that contribute to athlete performance, including physical, technical, psychological, and environmental factors. The literature review was conducted by searching and analyzing 14 relevant scientific articles, obtained through the publish or perish (POP) database and google scholar. The results show that physical condition, strength, endurance, agility, and speed, are the main elements in improving athlete performance. Psychological aspects, motivation and mental resilience, also affect the competitiveness and consistency of athlete performance in matches. Technical factors, which include playing skills such as serving, passing and blocking, and tactical factors, such as game strategy, also have a significant impact on match results. Environmental conditions, such as sand and weather characteristics, influence the effectiveness of movement and the energy expended by athletes. These findings provide implications for coaches and athletes in designing more comprehensive training programs with a sports science-based approach. An effective training strategy should consider the balance between physical, psychological, technical, and environmental factors to optimize the performance of beach volleyball athletes.